An exploratory analysis of the ability of a cefepime trough concentration greater than 22 mg/L to predict neurotoxicity. Issue 2 (February 2016) - Rhodes, Nathaniel J.; Kuti, Joseph L.; Nicolau, David P.; Neely, Michael N.; Nicasio, Anthony M.; Scheetz, Marc H.
Abstract: Introduction: Cefepime trough concentrations >22 mg/L (T>22 ) have been associated with neurotoxicity in a single study. Patients and methods: Neurotoxicity outcomes for 28 cefepime-treated adult patients with febrile neutropenia were abstracted from the literature. The precision of T>22 to predict neurotoxicity was quantified using 95% confidence intervals. Thirty-two cefepime-treated patients contributed serum concentrations for a pharmacokinetic model, fit using the Nonparametric Adaptive Grid algorithm within the Pmetrics package for R. Concentration-time curves were simulated for common dosing schemes and 3 renal dispositions. Probabilities of neurotoxicity and numbers needed to harm were calculated from simulations according to the proposed pharmacokinetic/toxicodynamic threshold of T>22 . Bayesian modeling was utilized to explore other pharmacokinetic parameters relationships with neurotoxicity. Results: The mean probability of neurotoxicity at T>22 was 51.4% (95% CI: 16.4–85.0%). Among the schemes and renal dispositions simulated, the combination of cefepime 2 g every 8 h and a creatinine clearance of 60 mL/min produced the greatest probability of neurotoxicity (48.3%). Estimated numbers needed to harm according to T>22 ranged from 2.1 to 18.5 persons. Explorations of maximal serum concentration and area under the curve demonstrated high levels of collinearity, making it impossible to identify trough concentrations as the driver of neurotoxicity. Discussion: T>22 had low precision as a predictive neurotoxic threshold. When a neurotoxic threshold of T>22 was assumed, projected neurotoxicity rates and numbers needed to harm greatly exceeded observed neurotoxicity rates in the general population and in high risk subpopulations. Other drug exposure metrics should be explored.